2013
DOI: 10.1179/2045772313y.0000000129
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and classifying quality-of-life tools for assessing pressure ulcers after spinal cord injury

Abstract: Many QoL outcome tools showed promise in being sensitive to the presence of pressure ulcers, but few of them have been validated for use with SCI. Prospective studies should employ more rigorous methods for collecting data on pressure ulcer severity and location to improve the quality of findings with regard to their impact on QoL. The Cardiff Wound Impact Schedule is a potential tool for assessing impact of pressure ulcers-post SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…QoL outcomes were then classified according to Dijkers' theoretical framework by one rater and verified by a second rater. 19,22 Similar to previous studies that classified QoL tools used to assess the influence of different SCI-related secondary conditions, [23][24][25] Dijkers' QoL framework was used to categorize outcome measures as being either objective or subjective and was used to provide a deeper understanding of the QoL constructs underlying each measure (see Figure 1). 19,22 Briefly described, the model categorizes measures into three categories: QoL as "utility," "achievements," and "subjective well-being.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QoL outcomes were then classified according to Dijkers' theoretical framework by one rater and verified by a second rater. 19,22 Similar to previous studies that classified QoL tools used to assess the influence of different SCI-related secondary conditions, [23][24][25] Dijkers' QoL framework was used to categorize outcome measures as being either objective or subjective and was used to provide a deeper understanding of the QoL constructs underlying each measure (see Figure 1). 19,22 Briefly described, the model categorizes measures into three categories: QoL as "utility," "achievements," and "subjective well-being.…”
Section: Methodsmentioning
confidence: 99%
“…20 QoL outcomes related to the influence of spasticity, pressure ulcers, and neurogenic bladder have been classified and documented using the aforementioned framework. [23][24][25] Objective measures are based on the assumption that there is widespread consensus on the constituents of QoL, 19,22 meaning that objective measures focus on external conditions and contain items that can be defined and quantified to reflect societal standards. Conversely, subjective measures follow a more individualistic approach and the assumption that QoL can only be judged by the individual or individual's experiencing it.…”
mentioning
confidence: 99%
“…Other researchers have utilized generic measures of health status and life satisfaction in studies examining HRQOL in individuals with PrUs and SCI. 35 For example, the Medical Outcomes Study Short Form-36 36 is a health status measure intended for a general health population but also contains items about such diverse areas as physical and emotional functioning. Hitzig et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hitzig et al . 35 also reported that the Life Situation Questionnaire-Revised 37 and the Ferrans and Powers Quality of Life Index for SCI v3, 38 two PRO measures of subjective HRQOL have been used in individuals with SCI and pressure ulcers, but neither of these instruments contain items that specifically address PrUs or how skin problems impact HRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…impact of neurogenic bladder on QoL). 6 Moreover, tools that are not developed specifically for SCI lack reliability and validity for application in SCI populations.…”
mentioning
confidence: 99%